Environmental Factors and Endometriosis - Grzegorz Polak (MDPI AG, 2021)
Endometriosis is a common disease, affecting up to 60–80% of women, with pelvic pain or/and infertility. Despite years of studies, its pathogenesis still remains enigmatic. Genetic, hormonal, environmental, and lifestyle-related factors may be involved in its pathogenesis. Thus, the design of the review was to discuss the possible role of environmental factors in the development of endometriosis. The results of individual studies greatly differ, making it very difficult to draw any definite conclusions. There is no reasonable consistency in the role of environmental factors in endometriosis etiopathogenesis.